Advanced Patellar Tendinopathy Is Associated With Increased Rates of Bone-Patellar Tendon-Bone Autograft Failure in Anterior Cruciate Ligament Reconstructions. Issue 7 (30th July 2018) - Lazarides, Alexander Leandros; Alentorn-Geli, Eduard; Vinson, Emily; Samuelsson, Kristian; Toth, Alison P.; Moorman, Claude T.; Garrett, William E.; Taylor, Dean C.
Objectives: Revision ACL reconstruction can be potentially devastating for a patient. As such, it is important to identify prognostic factors placing patients at increased risk for re-rupture. There are no data on the effects of patellar tendonopathy on failure of ACL reconstruction when using bone-patellar tendon-bone (BPTB) autograft. The purpose of this study was to investigate the effects of patellar tendinopathy on the risk of graft failure in primary ACL reconstruction when using BPTB autograft. Methods: All patients undergoing ACL reconstruction at a single institution from 2005 to 2015 were examined. A total of 168 patients undergoing primary BPTB autograft for primary ACL reconstruction were identified. Patient MRIs were reviewed for the presence and grade of patellar tendinopathy by two musculoskeletal fellowship-trained radiologists; both were blinded to the aim of the study, patient demographics, surgical details and outcomes. Patients were divided into two cohorts: failure and non-failure of the ACL graft, defined as rupture of the ACL graft. Statistical analyses were run to examine the role of patellar tendinopathy in failure of ACL reconstruction using BPTB autograft. Results: At a mean follow up of 18 months, there were 7 (4.2%) patients with graft failure. Moderate or high-grade patellar tendinopathy was associated with ACL graft failure (p=0.011). Age, gender and side of reconstruction were not associated with risk of re-rupture, though the majority of patients in our study who failed were younger than 20 years of age. Use of patellar tendon with moderate to severe tendinopathy was associated with a relative risk of rupture of 6.1 as compared to autograft tendon without tendinopathy (95% CI 1.37-27.3). Conclusion: The presence of moderate or severe patellar tendinopathy significantly increases the risk of graft failure when using BPTB autograft for primary ACL reconstruction. Consideration of patellar tendinopathy should be made when determining the optimal graft choice for patients undergoing primary ACL reconstruction with autograft tendons.